Communicating the League of Nations - United Nations (United Nations, 2024)
The volume aims to contribute to a deeper understanding of the League of Nations (1920-1946) as an international organization with complex transnational communication relations from a perspective of communication researchers. The authors focused on the reconstruction of internal communication processes within the Information Section as well as its strategies of external public communication The complex relationships between organized information practices of the Information Section and the profession and practices of League of Nations’ journalism can be understood as a co-evolution of journalism, public relations and press work. By the normative guidelines of the “principle of publicity” and the concept of “open diplomacy” media-mediated public communication, preferably via the press, was defined as an important factor for the legitimization of the organization and politics of the League of Nations.